2023
DOI: 10.1088/1475-7516/2023/01/017
|View full text |Cite
|
Sign up to set email alerts
|

Excess of lensing amplitude in the Planck CMB power spectrum

Abstract: Precise measurements of the Planck cosmic microwave background (CMB) angular power spectrum (APS) at small angles have stimulated accurate statistical analyses of the lensing amplitude parameter A L. To confirm if it satisfies the value expected by the flat-ΛCDM concordance model, i.e. A L = 1, we investigate the spectrum difference obtained as the difference of the measured Planck CMB APS and the Planck best-fit ΛCDM APS model. To know if this residual spectrum corresponds … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Among these are the low-quadrupole amplitude of the CMB angular power spectrum (Bennett et al 2003;Jarosik et al 2011), the alignment of some low-order multipoles (de Oliveira-Costa et al 2004;Bielewicz et al 2004Bielewicz et al , 2005Schwarz et al 2004;Land & Magueijo 2005;Abramo et al 2009;Polastri et al 2015), the lack of large-angle temperature-temperature (TT) correlations (Schwarz et al 2004(Schwarz et al , 2016Copi et al 2006Copi et al , 2009Bernui et al 2006), the parity asymmetry (Kim & Naselsky 2010;Gruppuso et al 2011;Aluri & Jain 2012;Hansen et al 2012;Zhao 2014;Aluri et al 2017), the cold spot (Vielva et al 2004;Cruz et al 2005;Bernui 2009;Gurzadyan et al 2014), and the north-south asymmetry (Eriksen et al 2004a,b;Hansen et al 2004a,b;Hoftuft et al 2009;Paci et al 2010;Pietrobon et al 2010;Bernui et al 2014;Gimeno-Amo et al 2023). Recently, it was also reported that the CMB lensing amplitude, A L , has a value higher than expected in the ΛCDM model (Calabrese et al 2008;Planck Collaboration VI 2020;Mokeddem et al 2023).…”
Section: Introductionmentioning
confidence: 92%
“…Among these are the low-quadrupole amplitude of the CMB angular power spectrum (Bennett et al 2003;Jarosik et al 2011), the alignment of some low-order multipoles (de Oliveira-Costa et al 2004;Bielewicz et al 2004Bielewicz et al , 2005Schwarz et al 2004;Land & Magueijo 2005;Abramo et al 2009;Polastri et al 2015), the lack of large-angle temperature-temperature (TT) correlations (Schwarz et al 2004(Schwarz et al , 2016Copi et al 2006Copi et al , 2009Bernui et al 2006), the parity asymmetry (Kim & Naselsky 2010;Gruppuso et al 2011;Aluri & Jain 2012;Hansen et al 2012;Zhao 2014;Aluri et al 2017), the cold spot (Vielva et al 2004;Cruz et al 2005;Bernui 2009;Gurzadyan et al 2014), and the north-south asymmetry (Eriksen et al 2004a,b;Hansen et al 2004a,b;Hoftuft et al 2009;Paci et al 2010;Pietrobon et al 2010;Bernui et al 2014;Gimeno-Amo et al 2023). Recently, it was also reported that the CMB lensing amplitude, A L , has a value higher than expected in the ΛCDM model (Calabrese et al 2008;Planck Collaboration VI 2020;Mokeddem et al 2023).…”
Section: Introductionmentioning
confidence: 92%
“…Because of the tension found in the values of the Hubble constant, H 0 , calculated with distinct cosmological probes in the late [24] and early universe [25], this panorama is now changing. Nowadays, there is a growing interest in examining diverse cosmological probes that can be used to measure the Hubble constant -and other cosmological parameters-and in the statistical analyses that can be done with them (see, e.g., [26][27][28][29][30][31][32][33][34][35][36][37]).…”
Section: Introductionmentioning
confidence: 99%
“…The Planck Legacy 2018 (PL18) release has confirmed the presence of an enhanced lensing amplitude in the CMB power spectra, which prefers a positively curved early Universe with a confidence level higher than 99% [4,5]. Besides, efforts to reconcile this lensing amplitude with spatial flatness by using baryon acoustic oscillation data were challenged due to a tension of 2.5 to 3σ in the curvature parameter between these data [6].…”
Section: Introductionmentioning
confidence: 99%